Research progress on risk factors of catheter-related thrombosis in elderly patients with peripherally inserted central catheters placement (老年患者PICC导管相关性血栓形成的危险因素研究进展) - ZHOU Keke (周可可) (中西医结合护理)
Peripherally inserted central catheters (PICC)-associated thrombosis is one of the common complications after PICC placement, which can seriously affect the quality of life and prognosis of elderly patients. The development of PICC catheter-associated thrombosis in elderly patients is closely related to a variety of factors, including the elderly patients' own conditions, disease-related factors, catheter-related factors, catheter placement-related factors, and drug-related factors. Tis paper reviews studies on PICC-associated thrombosis in elderly patients form perspectives of current research status, development mechanism and related risk factors, in order to provide a reference for medical staff to diagnose and prevent PICC catheter-related thrombosis in the early stage. (经外周静脉穿刺中心静脉置管(PICC)相关性血栓(PICC-CRT)是 PICC 置管后常见的并发症之一, 严重影响老年患者的生活质量和预后。老年患者PICC-CRT的形成与多种因素密切相关, 主要包括老年患者自身因素、疾病相关因素、导管相关因素、置管相关因素以及药物相关因素。本研究综述了老年患者 PICC-CRT 形成的危险因素研究现状, 包括老年患者 PICC 导管相关性血栓发生的现状、形成的机制以及相关危险因素, 旨在为医务人员针对血栓相关危险因素进行早期识别提供参考, 以期为 PICC 导管相关性血栓的预防提供科学依据。)